Exploring the Potential of Gender Parity to Promote Economic Growth - Devadas, Sharmila; Kim, Young Eun (World Bank, Washington, DC, 2020)
Narrowing the gender gap is critical to sustainable and inclusive growth. This brief discusses how moving toward gender equality can improve female labor force participation, human capital, and total factor productivity, leading to higher economic growth. The analysis simulates the cross-country impact of increasing female labor force participation and education on GDP growth for the next three decades. In practice, achieving substantial gains in gender equality across generations will require sustained efforts to reset gender norms, starting with the young, and to increase women's economic participation and voice in society in areas of influence.